Musique baroque ? - Haas, Frédérick 1969- (Paris Les Belles lettres, 2025)
In the 17th and 18th centuries, Europe was filled with music. Everywhere, music was being organised, developed and structured, under the influence of great founders: Monteverdi, ‘Inventor of the Opera’, Rameau, ‘Founder of Harmony’, J.S. Bach, ‘Father of all Music’, and other well-known names: Couperin, Vivaldi, Handel, Purcell, Lully... The music of this period, known in the meantime as “baroque music”, underwent a major revival in the 20th century and is now more widely performed than ever. It has an important place in the programming of concert halls and radio stations, and reaches a large and eclectic audience. Faced with this enthusiasm, the time has come to take a step back: can we define precisely what baroque music is? Why play it today? On what can we base the regeneration of practices that will continue to nourish the fascination of musicians and listeners? This book looks at compositional techniques, ornamentation and basso continuo, our relationship with time, the written word and historical sources, the musician's relationship with his or her instrument and what makes it a vehicle for intensity and expression. A book for music lovers and musicians, to help them understand, listen to and play Baroque music better. (Translated with DeepL.com)
Keywords: Baroque; Music history; Music philosophy and esthetics; Composing; Musical interpretation